Extreme fire spread events and area burned under recent and future climate in the western USA - Coop, Jonathan D., author; Parks, Sean A., author; Stevens-Rumann, Camille S., author; Ritter, Scott M., author; Hoffman, Chad M., author; John Wiley & Sons Ltd, publisher (Colorado State University. Libraries, 2022)
Aim: Wildfire activity in recent years is notable not only for an expansion of total area burned but also for large, single-day fire spread events that pose challenges to ecological systems and human communities. Our objectives were to gain new insight into the relationships between extreme single-day fire spread events, annual area burned, and fire season climate and to predict changes under future warming. Location: Fire-prone regions of the western USA. Time period: 2002 2020; a future +2°C scenario. Methods: We used a satellite-derived dataset of daily fire spread events and gridded climate data to assess relationships between extreme single-day fire spread events, annual area burned, and fire season maximum temperature, climate moisture deficit, and vapour pressure deficit. We then developed models to predict fire activity under a 2°C warming scenario. Results: Extreme single-day fire spread events >1,100 ha (the top 16%, >1 SD) accounted for 70% of the cumulative area burned over the period of analysis. The variation in annual area burned was closely tied to the number and mean size of spread events and distributional skewness towards more large events. For example, we identified 441 extreme events in 2020 that together burned 2.2 million ha across our study area, in contrast to an average of 168 per year that burned 0.5 million ha annually between 2002 and 2019. Fire season climate variables were correlated with the annual number of extreme events and area burned. Our models predicted that the annual number of extreme fire spread events more than double under a 2°C warming scenario, with an attendant doubling in the area burned. Conclusions: Exceptional fire seasons like 2020 will become more likely, and wildfire activity under future extremes is predicted to exceed anything yet witnessed. Safeguarding human communities and supporting resilient ecosystems will require new lines of scientific inquiry, new land management approaches and accelerated climate mitigation efforts.
Keywords: climate change; extreme wildfire event; fire behaviour; fire run; fire suppression; megafire